PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PUZZLE SISWA KELAS IV SD - Ferna Setiana; Theresia Sri Rahayu; Wasitohadi , (Jurnal Karya Pendidikan Matematika, 2019)
This study aims to improve student mathematics learning outcomes and describe the steps of the Problem Based Learning) model assisted by media puzzles. The subject of this study was in grade IV SD N Kecandran 01 Salatiga as many as 34 students. The method used is Class Action Research in two cycles. In this study, the data collection is used, namely documentation, observation, and written tests. The data analysis technique used is quantitative and qualitative descriptive techniques. The results showed that there was an increase in student learning outcomes seen in the pre-cycle of 34 students there were 15 students or 41% who completed with an average value of 61. Then the results of the first cycle increased to 24 students or 70% with an average value of 68, then in cycle II it increased again to 30 students or 89% with an average value of 80.